2021
DOI: 10.54808/jsci.19.08.198
|View full text |Cite
|
Sign up to set email alerts
|

Case Method in the Study of Information Technologies and IT Project Management

Abstract: The paper shows the features of the application of the case method in the study of the discipline of IT project management for students majoring in the field of Information Technology. This work analyzes some of the difficulties associated with the limited use of case studies in the field of IT. An original solution to the problem of combining flexible technologies for the development of the project itself on the basis of a case study and methods of studying and applying special software for IT project managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…The assignment of learning the case method model provides students experiences to identify and analyze cases of electrical disturbances to assist them in designing a protection system. The results of this study support the superiority of the case method in engineering learning, as shown by evidence from previous studies [17], [25]. Learning by combining theory and practice in small group assignments, providing materials, theories, illustrations, and assignments for solving cases is the strength of this model in improving student learning outcomes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The assignment of learning the case method model provides students experiences to identify and analyze cases of electrical disturbances to assist them in designing a protection system. The results of this study support the superiority of the case method in engineering learning, as shown by evidence from previous studies [17], [25]. Learning by combining theory and practice in small group assignments, providing materials, theories, illustrations, and assignments for solving cases is the strength of this model in improving student learning outcomes.…”
Section: Discussionsupporting
confidence: 82%
“…Figure 1 shows the research flow. The implementation of virtual multimediaassisted learning followed the rules of multimediabased learning [12], while the assignment treatment followed the case method rule [17], [18] and the team-based project [8], [20]. The test instrument for learning outcomes for mastery of concepts was developed in the form of an objective test that went through a validity and reliability test, while the competency learning outcomes for developing an electrical protection system used a test instrument for a project report.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) ідентифікування (передбачає визначення відхилень параметрів від критеріїв і / або стан дартів, формулювання діагнозу) [9].…”
Section: виклад основного матеріалу дослідження з повним обгрунтуванн...unclassified